2019
DOI: 10.35759/janmplsci.v40-3.2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamique de l’occupation du sol de la commune de Téssékéré de 1984 à 2015 (Ferlo Nord, Sénégal)

Abstract: Dynamique de l’occupation du sol de la commune de Téssékéré de 1984 à 2015 (Ferlo Nord, Sénégal) Diarra SYLLA1,2, Taibou BA2, Mariama Dalanda DIALLO3,4, Tamsir MBAYE5, Aly DIALLO6, Jean Luc PEIRY3,7, Aliou GUISSÉ1,3* 1Département de Biologie végétale, Faculté des Sciences et Techniques, Université Cheikh Anta Diop de Dakar, BP. 5005 Fann, Dakar, Sénégal 2Centre de Suivi Écologique pour la gestion des ressources naturelles (CSE), Fann Résidence, Rue Léon Gontran Damas, Dakar, Sénégal 3Observatoire Hommes-Mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…The rainfall deficit on the study areas recorded varies from 11% to 20% and the lost of vegetative activities through the vegetation index is between 4% and 8.5% [17]. These results are in agreement with the works of ( [6] [9] [11] [15] [74]) in the Ferlo region (north of Senegal).…”
Section: Analysis Of the Land Cover Dynamic In The Senegalese Great G...supporting
confidence: 87%
“…The rainfall deficit on the study areas recorded varies from 11% to 20% and the lost of vegetative activities through the vegetation index is between 4% and 8.5% [17]. These results are in agreement with the works of ( [6] [9] [11] [15] [74]) in the Ferlo region (north of Senegal).…”
Section: Analysis Of the Land Cover Dynamic In The Senegalese Great G...supporting
confidence: 87%
“…Today, the oldest plantations in the Senegalese GGW are 14 years old and, for most of them, protection was lifted after nine to 11 years. The study of land use dynamics in the first GGW intervention areas in Senegal showed that forestry areas increased from 0.08% in 1984 to 2.66% in 2015 thanks, at least in part, to the plantations implemented under the program (Sylla et al 2019b). The results of these developments remain, to date, modest because of the low recovery and survival rates of seedlings in the Sahel (Bernardino et al 2020) and, above all, the long growing time of most of the selected Sahelian species (Wade 2020).…”
Section: Acceleration and Timing Of Ecological Restorationmentioning
confidence: 99%
“…We identified generally allogenic forest succession by means of both natural and anthropogenic events (Dendoncker & Vincke 2020; Vincke et al 2010; Gonzales 1997; Poupon 1980). Drought and human pressure were the primary causes leading to decrease of vegetation cover over nearly 15% of the forested area over a period of 30 years (Sylla et al 2019). Tree population declines were also due to low natural regeneration of many trees species, and a high mortality rate following plantation (FAO 2000).…”
Section: The Restoration Challenge In the Sahel: Temporal Dynamics An...mentioning
confidence: 99%